Social Effects of Lato-Lato Games on Children of SD/MI Age - Pramudia Ananda; Windi Melisa; Falih Daffa (Yayasan Zia Salsabila, 2023)
Lato-lato is a game with two heavy objects made of plastic. In its development, playing on average has various impacts on the development of elementary school children’s behavior. The purpose of this research is to review whether playing lato-lato affects social impact among SD/MI children, as well as to find out what are the impacts of the set game on the development of children’s behavior. This research uses a meta analysis design. In this study, data collection was obtained from articles in online journals. In addition to using the meta analysis design, the authors also used descriptive research methods with a quantitative approach. This approach emerges from a theoretical framework. Main ideas and understanding of the author based on his experience. Then developed into problems and solutions to problems proposed to obtain the truth or assessment in the form of empirical data support in the field. The result obtained from this study indicate that children who are addicted to playing lato-lato then to show changes in behavior, especially in changes in social attitudes that are more emotional.